[latex]1) \ \sqrt{6-2 \sqrt{5} } - \sqrt{9+4 \sqrt{5} } \\ 2) 3- \sqrt{x-1} = \sqrt{6-x} [/latex]

[latex]1) \ \sqrt{6-2 \sqrt{5} } - \sqrt{9+4 \sqrt{5} } \\ 2) 3- \sqrt{x-1} = \sqrt{6-x} [/latex]
Гость
Ответ(ы) на вопрос:
Гость
[latex] \sqrt{ \sqrt{5} ^{2}-2 \sqrt{5} + 1^{2} } - \sqrt{ \sqrt{5} ^{2}+4 \sqrt{5}+ 2^{2} } = \sqrt{5} -1- \sqrt{5} -2=-3 \\ \sqrt{x-1} + \sqrt{6-x} =3 \\ 5+2 \sqrt{(x-1)(6-x)} =9 \\ (x-1)(6-x)=4 \\ x^{2} -7x+10=0 \\ x_{1} =2 \\ x_{2} =5[/latex]
Гость
1)[latex] \sqrt{( \sqrt{5} -1)^2} - \sqrt{( \sqrt{5} +2)^2} = \sqrt{5} -1- \sqrt{5} -2=-3[/latex] 2)ОДЗ  x≥1 U x≤6⇒x∈[1;6] Возведем в квадрат 9-6[latex] \sqrt{x-1} [/latex]+х-1=6-х 6[latex] \sqrt{x-1} [/latex]=2х+2 3[latex] \sqrt{x-1} [/latex]=ч+1 Возведем в квадрат 9(х-1)=х²+2х+1 х²-7х+10=0 х1+х2=7 и х1*х2=10 х1=2 и х2=5
Не нашли ответ?
Ответить на вопрос
Похожие вопросы